(untitled) (Bangladesh Journal of Agricultural Research, 2015)
The experiment on brinjal (Solanum melongena L.) having seven growth regulators viz., control, 30 ppm GA3 , 40 ppm GA3, 50 ppm GA , 20 ppm NAA, 40 ppm NAA, and 60 ppm NAA and two varieties viz., BARI Begun-5 and BARI Begun -10 was conducted at the field of Plant Physiology Section of HRC during the rabi season (November 2011 to May 2013) to find out the suitable variety responsive to growth regulators and to determine the suitable dose of growth regulator for brinjal production. The GA3 (Gibberellic acid) and NAA (Naphthalene acetic acid) had no significant effect on plant height and stem diameter at the end of the crop period and days to 100% flowering. NAA 40 ppm produced highest percentage of long and medium styled-flower, leaf photosynthesis and Fv/Fm (efficiency of photosystem II), number of fruits /plant and fruit yield (45.50 t/ha). The variety BARI Begun-5 was earlier to 100% flowering which took 44 days after transplanting which outyielded BARI Begun-10. NAA 40 ppm coupled with BARI Begun-5 gave the maximum Fv/Fm, long-styled flower percent, number of fruits/plant, and the highest fruit yield (49.73 t/ha). DOI: http://dx.doi.org/10.3329/bjar.v39i3.21983 Bangladesh J. Agril. Res. 39(3): 397-405, September 2014